2009
DOI: 10.1590/s0103-21002009000800013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do grau de satisfação de pacientes renais crônicos em hemodiálise

Abstract: Objective:To identify the level of satisfaction in patients with chronic renal disease on hemodialysis regarding their care and the physical structure of the hemodialysis unit of the Hospital "de Base" of Sao José do Rio Preto, SP. Methods: This descriptive study used a Likettype scale to collect data from 81 patients from the nephrology department. Results: Almost all patients were very satisfied (53 %) or satisfied (47%) regarding their care and the physical structure of the hemodialysis unit. A few limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
1
0
4
Order By: Relevance
“…The epidemiological profile of the patients undergoing Renal Replacement Therapy (RRT) in Brazil in the period 2000 - 2004 showed that most (57%) of those who started RRT by Hd were men, with a mean age of 53 years old (sd± 17) and a median age of 54 years old ( 16 ) . The results of other studies held with patients receiving the same therapy also showed a predominance of men ( 17 - 19 ) .…”
Section: Discussionmentioning
confidence: 66%
“…The epidemiological profile of the patients undergoing Renal Replacement Therapy (RRT) in Brazil in the period 2000 - 2004 showed that most (57%) of those who started RRT by Hd were men, with a mean age of 53 years old (sd± 17) and a median age of 54 years old ( 16 ) . The results of other studies held with patients receiving the same therapy also showed a predominance of men ( 17 - 19 ) .…”
Section: Discussionmentioning
confidence: 66%
“…Dentre as dificuldades da avaliação menciona-se, principalmente, a existência de diferentes abordagens conceituais sobre a satisfação do usuário. Definem a satisfação do usuário como avaliações positivas individuais de distintas dimensões do cuidado à saúde (ODININO; GUIRARDELLO, 2010); obtida por meio de um conjunto amplo e heterogêneo de pesquisas, com o objetivo de saber a opinião dos usuários de serviços (CESARINO et al, 2009); ou que a satisfação pode ser vista pela reação que usuários têm diante do contexto, do processo e do resultado global de sua experiência relativa ao serviço, incluindo características sociodemográficas, status físico e psicológico, atitudes e expectativas sobre estrutura, processo e resultados do cuidado (SISSON et al, 2011).…”
Section: Avaliação Dos Serviços E Satisfação Dos Usuários Na Saúdeunclassified
“…Ressaltando a minimização de eventos adversos relacionados à infecção e à garantia da segurança do paciente. Outrora, no estudo de Cesarino et al 8 apenas 50,6% afirmaram que os problemas dos pacientes são avaliados e registrados por uma enfermeira. De acordo com autores especialistas em nefrologia, [9][10] todo paciente deve ter o tratamento supervisionado por uma equipe multiprofissional e especializada, tendo como objetivo condutas de desenvolvimentos diante do agravamento ou para retardar a evolução da doença.…”
Section: Princípios éTicosunclassified